Social Stratification of Betao Riase Village Community Pitu Riawa District Sidenreng Rappang District South Sulawesi - Kadir, Moch. Dienul Fajry; Sosiawan, Aryo; Nain, Umar (Jurnal Pallangga Praja (JPP), 2024)
Social stratification is a form of concept in sociology that discusses grouping, classifying, and dividing social groups and a community in society into a certain class, level, or strata that form a certain layer. This research was conducted to find out how the differences in social class and interactions between members of the Betao Riase village community. The method used in this study is a qualitative method with in-depth interview techniques. There are three caste differences in the Betao Riase village community, namely Andi, Ie and Ua. These three castes are distinguished by the shape of the house and ownership of plantation and agricultural land. Classes in the village community only show that there is a division of caste and the number of land ownership but this does not interfere with social interaction between members of the village community. Caste differences are not a problem and people can still live together comfortably and peacefully.